2019
DOI: 10.1111/crj.13027
|View full text |Cite
|
Sign up to set email alerts
|

Do the global lung function initiative reference equations reflect a sample of adult Middle Eastern population?

Abstract: Introduction The global lung function initiative (GLI) 2012 introduced new multi‐ethnic spirometry reference values for numerous ethnicities. Objectives The aim of this study was to investigate the suitability of the GLI reference values for the adult Jordanian population. Methods About 1875 (1029 females and 846 males) healthy non‐smoking adults were enrolled from several locations in Jordan. Spirometry tests were performed. z‐scores and predicted normal values were calculated for each participant using GLI 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…To summarize, the results of this study indicated that similar to other studies conducted in several countries in Europe, 26‐28 the GLI 2012 equations for Caucasians demonstrated a reasonable fit to our data; as the study results indicate that the Caucasian equation was more suitable for the Jordanian school‐aged children when compared with the other or mixed. This contraindicate our previous results 29 that found that the GLI 2012 for other or mixed was a better representation to the adult Jordanian when compared with the Caucasian equation, this emphasizes the importance of evaluating the applicability of GLI 2012 Caucasians and other or mixed to older children in Jordan and highlights the importance of long‐term longitudinal studies to evaluate changes occurring in lung growth and factors that may influence it in Jordan.…”
Section: Discussioncontrasting
confidence: 72%
“…To summarize, the results of this study indicated that similar to other studies conducted in several countries in Europe, 26‐28 the GLI 2012 equations for Caucasians demonstrated a reasonable fit to our data; as the study results indicate that the Caucasian equation was more suitable for the Jordanian school‐aged children when compared with the other or mixed. This contraindicate our previous results 29 that found that the GLI 2012 for other or mixed was a better representation to the adult Jordanian when compared with the Caucasian equation, this emphasizes the importance of evaluating the applicability of GLI 2012 Caucasians and other or mixed to older children in Jordan and highlights the importance of long‐term longitudinal studies to evaluate changes occurring in lung growth and factors that may influence it in Jordan.…”
Section: Discussioncontrasting
confidence: 72%
“…This present study is part of a project involving three parts. The first and two parts, which were recently published, aimed at testing the applicability of the GLI‐ 2012 norms on a sample of healthy adults aged ≥ 18 years 16 and school‐age children (age: 6–13 years) 13 living in Jordan. The third part is the objective of this study.…”
Section: Methodsmentioning
confidence: 99%
“…13 However, the GLI-2012 Caucasian equations showed a better representation in the younger group when compared with the current studied age group. 13 Moreover, previous work that validated the GLI-2012 equations in Jordanian adults 16 indicated that the GLI-2012 Other or Mixed had a better representation for the Jordanian adults. 16 The results of these three studies indicate that there is a slower pulmonary growth rate and emphasizes the need for long-term studies to evaluate the changes in lung growth rates among the Jordanian population and factors that may influence these.…”
Section: F I G U R E 1 Recruitment Chart Flowmentioning
confidence: 98%
“…Many studies have evaluated the GLI spirometry equations and recommended their use in clinical practice [ 8 12 ]. However, not all validation studies on Caucasians have concluded that GLI provides an accurate fit [ 13 15 ]. Comparison of the GLI reference equations on spirometry to those of the 1993 ERS reference values convincingly demonstrated that the former outperformed the latter to describe the data of a large Swedish cohort [ 16 ].…”
Section: Introductionmentioning
confidence: 99%